2010
DOI: 10.1371/journal.pone.0009278
|View full text |Cite
|
Sign up to set email alerts
|

A Global Analysis of the Effectiveness of Marine Protected Areas in Preventing Coral Loss

Abstract: BackgroundA variety of human activities have led to the recent global decline of reef-building corals [1], [2]. The ecological, social, and economic value of coral reefs has made them an international conservation priority [2], [3]. The success of Marine Protected Areas (MPAs) in restoring fish populations [4] has led to optimism that they could also benefit corals by indirectly reducing threats like overfishing, which cause coral degradation and mortality [2], [5]. However, the general efficacy of MPAs in inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
214
1
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(249 citation statements)
references
References 49 publications
17
214
1
5
Order By: Relevance
“…Recent analyses suggest that marine protected areas may promote local processes, such as herbivory and coral recruitment (39,40), that limit macroalgal proliferation and promote coral recovery, thereby bolstering coral resilience to large-scale disturbance (7,8,11,41,42). However, because several allelopathic macroalgae (e.g., Dictyota, Chlorodesmis, Galaxaura, Lobophora, Halimeda, Ochtodes) also contain toxins that deter some herbivores (43), developing effective marine reserves may require protecting a diverse herbivore guild that includes species that consume chemically defended macroalgae (18,33,43).…”
Section: Discussionmentioning
confidence: 99%
“…Recent analyses suggest that marine protected areas may promote local processes, such as herbivory and coral recruitment (39,40), that limit macroalgal proliferation and promote coral recovery, thereby bolstering coral resilience to large-scale disturbance (7,8,11,41,42). However, because several allelopathic macroalgae (e.g., Dictyota, Chlorodesmis, Galaxaura, Lobophora, Halimeda, Ochtodes) also contain toxins that deter some herbivores (43), developing effective marine reserves may require protecting a diverse herbivore guild that includes species that consume chemically defended macroalgae (18,33,43).…”
Section: Discussionmentioning
confidence: 99%
“…Increased CO 2 levels in the atmosphere drive higher CO 2 levels in ocean water reducing pH that in turn hampers formation of the calcium carbonate skeletons of some coral species (Ries, Stanley & Hardie, 2006, Fine & Tchernov, 2007Riegl, Bruckner, Coles, Renaud & Dodge, 2009). Marine Protected Areas have the potential to offer some relief from the local stressors thereby increasing potential resilience of the coral community to impacts associated with climate change (Riegl et al, 2009;Selig & Bruno, 2010;Riegl et al, 2013). The purpose of this study is to monitor the coral reef community in Grenada's MPA as various management practices are implemented.…”
Section: Discussionmentioning
confidence: 99%
“…MPAs have proven effective in decreasing biological stresses on corals, but their capacity to reduce physical stresses, such as elevated SST, appear to be limited (Mumby and Steneck 2008). A worldwide meta-analysis contrasting change in percent coral cover between MPAs and non protected areas concluded that MPAs were effective in preventing coral cover loss (Selig and Bruno 2010). However, the analysis of Selig and Bruno, (2010) also showed that coral cover decreased significantly after the 1998 mass bleaching event within MPAs in the Indo-Pacific region underscoring that MPAs offer little protection from rising SST related phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recent increase in frequency of large-scale, mass coral bleaching events where entire regions are affected is understood to be related to global warming (Hoegh-Guldberg andBruno 2010, Lough andvan Oppen 2010). As a result, coral reefs around the planet have experienced significant live tissue cover decline (McClanahan et al 2002, West and Salm 2003, Hughes et al 2007, Selig and Bruno 2010). Yet, data on the demographic consequences of bleaching events on coral populations is mostly lacking.…”
Section: Introductionmentioning
confidence: 99%